2021
DOI: 10.1101/2021.01.25.428167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defects in translation-dependent quality control pathways lead to convergent molecular and neurodevelopmental pathology

Abstract: Translation-dependent quality control pathways such as no-go decay (NGD), non-stop decay (NSD) and nonsense-mediated decay (NMD) govern protein synthesis and proteostasis by resolving non-translating ribosomes and preventing the production of potentially toxic peptides derived from faulty and aberrant mRNAs. However, how translation is altered and the in vivo defects that arise in the absence of these pathways are poorly understood. Here, we show that the NGD/NSD factors Pelo and Hbs1l are critical for cerebel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 156 publications
0
7
0
Order By: Relevance
“…The intriguing aspect is why decreased protein expression of ribosomal rescue proteins, like HBS1L, elicits tissue-specific phenotypes. While Hbs1l tm1a/tm1a hypomorph mice do not display overt neurodegenerative phenotype (17), likely due to residual protein expression, an equivalent reduction of Hbs1l leads to retinal dystrophy in these mice. This difference may be partially explained by the extraordinary demand of protein synthesis for disc membrane and outer segment renewal in the retina (36)(37)(38) along with limited actively translating ribosomes due to Hbs1l depletion (16).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The intriguing aspect is why decreased protein expression of ribosomal rescue proteins, like HBS1L, elicits tissue-specific phenotypes. While Hbs1l tm1a/tm1a hypomorph mice do not display overt neurodegenerative phenotype (17), likely due to residual protein expression, an equivalent reduction of Hbs1l leads to retinal dystrophy in these mice. This difference may be partially explained by the extraordinary demand of protein synthesis for disc membrane and outer segment renewal in the retina (36)(37)(38) along with limited actively translating ribosomes due to Hbs1l depletion (16).…”
Section: Discussionmentioning
confidence: 90%
“…Additional mouse studies show that Hbs1l is required for mammalian embryogenesis and complete loss of Hbs1l results in embryonic lethality (17). We and others have shown that the deletion of Hbs1l leads to a tissue-specific reduction in its partner protein Pelo, which alters transcription regulation and reprograms the translatome (16,17).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations